2023
DOI: 10.1021/acs.langmuir.2c03082
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Peptide Analogs of Apolipoprotein A-I Reveal Tunable Features of Nanodisc Assembly

Abstract: Nanodisc (ND)-forming membrane scaffold proteins or peptides developed from apolipoprotein A-I (apoA-I) have led to considerable promise in structural biology and therapeutic applications. However, the rationale and regularity characteristics in peptide sequence design remain inconclusive. Here, we proposed a consensus-based normalization approach through the reversed engineering of apoA-IΔ1–45 to design reconfigurable apoA-I peptide analogs (APAs) for tunable ND assembly. We present extensive morphological va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In addition to exploring the mechanism of stability, molecular dynamics can also be used to design protein therapeutics with improved stability [208] . In our latest work, we developed a consensus-based normalization approach for designing reconfigurable apoA-I peptide analogs (APAs) to create tunable ND assemblies, with potential implications for structural biology and therapeutics [209] . We generated 15 divergent APAs and demonstrated that APA design influences ND diameter and stability through factors such as tandem repeats, sequence composition, and lipid-to-APA ratio.…”
Section: Computational Methods For the Rational Design Of Protein-bas...mentioning
confidence: 99%
“…In addition to exploring the mechanism of stability, molecular dynamics can also be used to design protein therapeutics with improved stability [208] . In our latest work, we developed a consensus-based normalization approach for designing reconfigurable apoA-I peptide analogs (APAs) to create tunable ND assemblies, with potential implications for structural biology and therapeutics [209] . We generated 15 divergent APAs and demonstrated that APA design influences ND diameter and stability through factors such as tandem repeats, sequence composition, and lipid-to-APA ratio.…”
Section: Computational Methods For the Rational Design Of Protein-bas...mentioning
confidence: 99%
“…26,41,42 The ability of ND to target macrophages was accomplished by DPPS, 43 and the ND assemblies were prepared according to a previously reported method with some modifications. 28 Briefly, 1,2-dipalmitoyl-sn-glycerol-3-phosphocholine (DPPC) and 1,2dipalmitoyl-sn-glycero-3-phospho-L-serine (DPPS) were dissolved in chloroform in a glass tube at a 9:1 molar ratio. Chloroform was dried using a gentle argon gas stream, and the tube was placed in a vacuum desiccator overnight to remove residual solvent.…”
Section: Author Informationmentioning
confidence: 99%
“…In addition, cell-level experiments revealed that KDM6B promoted the differentiation of BMDM into M2. Endogenous and synthetic lipoproteins, such as high-density lipoprotein (HDL) nanodiscs, have emerged as a promising drug delivery system (DDS) for small molecules, peptides, and nucleic acids due to their inherent long half-life in vivo and passive targeting characteristics. , Based on our recently reported work on reprogrammable peptide analogs of apolipoprotein A-I (APA) for tunable nanodisc engineering, we propose a GSK-J4-loaded nanodisc (ND-GSK-J4) targeting macrophages in bone by introducing a bone formation surface-targeting peptide-modified membrane scaffold (SDSSD-APA) and administered it to mice. After administration, it was noted that macrophages in the bone marrow of mice tended to exhibit the M1 type, and bone loss increased.…”
Section: Introductionmentioning
confidence: 99%
“…The assembly involves the self-assembly of phospholipids and MSPs, and the correct protein-to-lipid ratio is crucial for ND integrity and function [150]. Factors such as lipid type, MSP variant, and assembly conditions necessitate optimization and significantly impact the assembly complexity and reproducibility [150,151], which are essential for complying with strict pharmaceutical regulations. Minor variations could alter ND properties, affecting their in vivo behavior and therapeutic efficacy, leading to batch variability and translational challenges.…”
Section: Complexity and Reproducibilitymentioning
confidence: 99%